2021
DOI: 10.1515/nanoph-2021-0133
|View full text |Cite
|
Sign up to set email alerts
|

Brief exposure of skin to near-infrared laser augments early vaccine responses

Abstract: Rapid establishment of herd immunity with vaccination is effective to combat emerging infectious diseases. Although the incorporation of adjuvant and intradermal (ID) injection could augment early responses to the vaccine, the current chemical or biological adjuvants are inappropriate for this purpose with their side effects and high reactogenicity in the skin. Recently, a near-infrared (NIR) laser has been shown to augment the immune response to ID vaccination and could be alternatively used for mass vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 89 publications
3
5
0
Order By: Relevance
“…Examination of antibody titers using the influenza vaccine mouse model showed that IgG antibody titers in the 1270 nm laser group tended to be higher on day 21 than in the ID only group and were significantly higher on day 56. However, similar to our previous report ( 41 ), the 1064 nm laser group in the present study elicited an early antibody production response at day 21. Interestingly, a similar trend was observed during the entire observation period from day 7 to day 112 ( Figure S1 ).…”
Section: Discussionsupporting
confidence: 92%
“…Examination of antibody titers using the influenza vaccine mouse model showed that IgG antibody titers in the 1270 nm laser group tended to be higher on day 21 than in the ID only group and were significantly higher on day 56. However, similar to our previous report ( 41 ), the 1064 nm laser group in the present study elicited an early antibody production response at day 21. Interestingly, a similar trend was observed during the entire observation period from day 7 to day 112 ( Figure S1 ).…”
Section: Discussionsupporting
confidence: 92%
“…Laser adjuvants deliver non-invasive laser beams to increase motility of antigen-presenting cells (APCs) or microfractional laser beams to create microthermal damages to enhance ID vaccine-induced immune responses. [33][34][35][36][37] Laser adjuvants demonstrated substantial adjuvant effects against seasonal influenza vaccination in preclinical animal models. [33][34][35][36][37] A near-infrared laser adjuvant has advanced to a pilot clinical test and was found to promote cutaneous immune cell trafficking without skin damage.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37] Laser adjuvants demonstrated substantial adjuvant effects against seasonal influenza vaccination in preclinical animal models. [33][34][35][36][37] A near-infrared laser adjuvant has advanced to a pilot clinical test and was found to promote cutaneous immune cell trafficking without skin damage. 38 Recently, we also reported an ablative fractional laser technology capable of alerting innate immune systems for more immunogenic vaccination without needle injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to systemic steroids which broadly suppress the immune response, PBM stimulates complexes of the mitochondrial respiratory chain to optimize and modulate the immune response, resulting in an improvement of its ability to eradicate infection via stimulation of the innate and adaptive immune cells [ 44 , 45 , 46 ], while providing an inhibitory effect on excessive inflammation [ 3 ]. Moreover, PBM can prompt cellular regeneration in every organ [ 47 , 48 , 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%